Letters From the Lost: A Memoir of Discovery - Helen Waldstein Wilkes (Our Lives: Diary, Memoir, and Letters, 2010)
On March 15, 1939, Helen Waldstein's father snatched his stamped exit visa from a distracted clerk to escape from Prague with his wife and child. As the Nazis closed in on a war-torn Czechoslovakia, only letters from their extended family could reach Canada through the barriers of conflict. The Waldstein family received these letters as they made their lives on a southern Ontario farm, where they learned to be Canadian and forget their Jewish roots. Helen Waldstein read these letters as an adult-this changed everything. As her past refused to keep silent, Helen followed the trail of the letters back to Europe, where she discovered living witnesses who could attest to the letters' contents. She has here interwoven their stories and her own into a compelling narrative of suffering, survivor guilt, and overcoming intergenerational obstacles when exploring a traumatic past.